2016
DOI: 10.1007/s40719-016-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Penetrating Trauma to the Major Abdominal Vessels

Abstract: Penetrating abdominal vascular injuries result in significant mortality. In the pre-hospital phase of care, Bscoop and run^is the optimal strategy while on-scene interventions are restricted only to basic airway maneuvers. Early in-hospital diagnosis and operative interventions are prerequisites for survival in vascular trauma. Hypotension and peritonitis following penetrating abdominal trauma mandate immediate access to the operating room with vascular surgery capabilities. Patients presenting in extremis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…11 These principles were originally described over a century ago, particularly in military theaters, and even today in the damage control setting, shunting may be the most prudent option. 12,13 Still, more contemporary studies have also shown endovascular interventions to be a potentially efficacious adjunct to delayed repair surgery.…”
Section: Historical Perspectivementioning
confidence: 99%
“…11 These principles were originally described over a century ago, particularly in military theaters, and even today in the damage control setting, shunting may be the most prudent option. 12,13 Still, more contemporary studies have also shown endovascular interventions to be a potentially efficacious adjunct to delayed repair surgery.…”
Section: Historical Perspectivementioning
confidence: 99%